microRNAs in neurons: manifold regulatory roles at the synapse - Siegel, Gabriele; Saba, Reuben; Schratt, Gerhard (Current opinion in genetics & development, 2011)
The regulation of synapse formation and plasticity in the developing and adult brain underlies a complex interplay of intrinsic genetic programs and extrinsic factors. Recent research identified microRNAs (miRNAs), a class of small non-coding RNAs, as a new functional layer in this regulatory network. Within only a few years, a network of synaptic miRNAs and their target genes has been extensively characterized, highlighting the importance of this mechanism for synapse development and physiology. Very recent data further provide insight into activity-dependent regulation of miRNAs, thereby connecting miRNAs with adaptive processes of neural circuits. First direct links between miRNA dysfunction and synaptic pathologies are emerging, raising the interest in these molecules as potential biomarkers and therapeutic targets in neurological disorders.